Silver Nanoparticle Synthesis Using Monosaccharides and Their Growth Inhibitory Activity against Gram-Negative and Positive Bacteria. (20th January 2014) - Pettegrew, Colin; Dong, Zheng; Muhi, M. Zubayed; Pease, Scott; Mottaleb, M. Abdul; Islam, M. Rafiq
Abstract : Using various monosaccharides as reductant, we synthesized Ag nanoparticles (NPs) in seconds employing the household microwave method described earlier. The Ag NPs containing colloidal solution showed distinctive colors with varying λ max . The sizes of the NPs formed varied significantly from 10 to 35 nm in good agreement with the localized plasmon resonance ranged from ~300 to ~600 nm. The antimicrobial properties of these NPs were compared in Gram-negative and positive bacteria in liquid culture. Gram-positive bacteria were highly susceptible compared to Gram-negative microbes—the additional lipopolysaccharide layer covering the peptidoglycan cell wall in the latter somewhat lessens the effect. The results indicated that larger NPs produced by glucose inhibited bacterial growth better than the smallest NPs produced by ribose. This may be attributed to the higher aggregation rate for larger NPs on cell wall. SEM analysis showed accumulation of NPs on cell surface and defect in budding, further supporting the cell wall interaction with Ag NPs. These observations suggested that the growth inhibition of Ag NPs is mediated by interfering with the bacterial cell wall peptidoglycan.